The global SF6 source inferred from long-term high precision atmospheric measurements and its comparison with emission inventories - Levin, Ingeborg; Naegler, T.; Heinz, Renate; Osusko, D.; Cuevas, E.; Engel, A.; Ilmberger, Johann; Langenfelds, R. L.; Neininger, B.; Rohden, C. v; Steele, L. P.; Weller, R.; et al. (Atmospheric chemistry and physics, 2010)
Emissions of sulphur hexafluoride (SF6), one of the strongest greenhouse gases on a per molecule basis, are targeted to be collectively reduced under the Kyoto Protocol. Because of its long atmospheric lifetime (estimated as 800 to 3200 years), the accumulation of SF6 in the atmosphere is a direct measure of its global emissions. Examination of our extended data set of globally distributed high-precision SF6 observations shows an increase in SF6 abundance from near zero in the 1970s to a global mean of 6.7 ppt by the end of 2008. In-depth evaluation of our long-term data records shows that the global source of SF6 decreased after 1995, most likely due to SF6 emission reductions in industrialised countries, but increased again after 1998. By subtracting those emissions reported by Annex I countries to the United Nations Framework Convention of Climatic Change (UNFCCC) from our observation-inferred SF6 source leaves a surprisingly large gap of more than 70-80% of non-reported SF6 emissions in the last decade. This suggests a strong under-estimation of emissions in Annex I countries and underlines the urgent need for independent atmospheric verification of greenhouse gases emissions accounting.